Architecture of Computing Systems - ARCS 2011 24th International Conference, Como, Italy, February 24-25, 2011. Proceedings - Berekovic, Mladen; Fornaciari, William; Brinkschulte, Uwe; Silvano, Cristina (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 24th International Conference on Architecture of Computing Systems, ARCS 2011, held in Lake Como, Italy, in February 2011. The 22 revised full papers presented in seven technical sessions were carefully reviewed and selected from 62 submissions. The papers are organized in topical sections on customization and application specific accelerators; multi/many-core architectures; adaptive system architectures; processor architectures; memory architectures optimization; organic and autonomic computing; network-on-chip architectures.